2020
DOI: 10.3390/en13174492
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate Conditions in Rooms: Their Impact on Mold Development in Buildings

Abstract: The publication concerns the problem of adopting proper environmental conditions in the assessment of mold development in the so-called thermal bridges in the form of corners. The paper discusses the factors determining the development of mold and the models that predict its growth. The conditions of the internal microclimate, which is used in hygrothermal diagnostics of walls, were also recalled. Thermal bridges are areas where mold development takes place, therefore the climatic conditions in the room taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…In this article, the improvement of the thermal envelope of the building was carried out in relation to the indicators of the internal microclimate in the building [12], its energy efficiency [13,14,15], and geometric data [16], as well as to the reasons of thermal bridges formation [17,18,19] and mold growth [7,20] in enclosures.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, the improvement of the thermal envelope of the building was carried out in relation to the indicators of the internal microclimate in the building [12], its energy efficiency [13,14,15], and geometric data [16], as well as to the reasons of thermal bridges formation [17,18,19] and mold growth [7,20] in enclosures.…”
Section: Discussionmentioning
confidence: 99%
“…Continued corrosion of the metal can occur if the relative humidity is greater than 80% while the temperature is above 0 • C at the surface. With regard to mould growth, studies point to a maximum relative humidity limit of 75% to prevent it, as reported by Zhan et al [19] based on studies [24][25][26].…”
Section: Introductionmentioning
confidence: 92%
“…SBS phenomenon commonly caused by the poor quality of temperature, humidity, and by the activity of spores, mycotoxins, and volatile compounds from toxic microorganisms such as fungus, bacteria, and other pathogenic organisms [9], [10]. However, many studies discussed that the microorganism, especially mold occurrence, is related to room microclimate [9], [11], [12].…”
Section: Introductionmentioning
confidence: 99%